THE INFLUENCE OF BRAND IMAGE AND E-WOM ON PURCHASE DECISION WITH TRUST AS A MEDIATING VARIABLE(A Study on Evangeline Perfume Users in Generation Y and Z) - Lutfi Sindy Yulitaningrum; Anik Lestari Andjarwati (Adisam Publisher, 2024)
Competitive business competition in the digital era means that entrepreneurs need to make careful efforts to win market competition. Brand Image, e-WOM and trust are needed to make purchasing decisions. This research aims to determine the influence of brand image and e-WOM on purchasing decisions through trust as a mediating variable in Evangeline perfume users generation Y and Z. This research is a type of quantitative research and uses non-probability sampling techniques with the path analysis method. Respondents in this research took a sample of 220 respondents who were women aged at least 17 years and had purchased Evangeline perfume at least twice in the last 2 months offline. The research results show that there is an influence of brand image and e-WOM on purchasing decisions through trust as a mediating variable for Evangeline perfume users.